Design and synthesis of ERα agonists: Effectively reduce lipid accumulation - Yang, Jinfei; Yao, Weiwei; Yang, Huihui; Shen, Yajing; Zhang, Yuanyuan (Frontiers in Chemistry, 2022)
In recent years, the incidence of nonalcoholic fatty liver disease (NAFLD) has been increasing worldwide. Hepatic lipid deposition is a major feature of NAFLD, and insulin resistance is one of the most important causes of lipid deposition. Insulin resistance results in the disruption of lipid metabolism homeostasis characterized by increased lipogenesis and decreased lipolysis. Estrogen receptor α (ERα) has been widely reported to be closely related to lipid metabolism. Activating ERa may be a promising strategy to improve lipid metabolism. Here, we used computer-aided drug design technology to discover a highly active compound, YRL-03, which can effectively reduce lipid accumulation. Cellular experimental results showed that YRL-03 could effectively reduce lipid accumulation by targeting ERα, thereby achieving alleviation of insulin resistance. We believe this study provides meaningful guidance for future molecular development of drugs to prevent and treat NAFLD.